Antibacterial Test Of Avocado Leaf Ethanol Extract (Persea americana Mill) On Propionibacterium Acne - Rosanto Tamba; Harsan Arifin Kasan; Ika Suryani Pangaribuan (International Journal of Health Engineering and Technology, 2024)
Avocado leaves are one plant that can be used as an antibacterial. The chemical content of flavonoids, alkaloids, tannins and saponins has the potential to inhibit bacterial growth. This research aims to determine the antibacterial activity of ethanol extract of avocado leaves against Staphylococcus aureus bacteria. This research uses laboratory experiments using samples of avocado leaf extract (Persea americana Mill). With concentrations of 20%, 40%, 60% and 80% using the diffusion method. The ability of avocado leaf extract to inhibit Staphylococcus aureus bacteria can be seen from the size of the inhibition zone, namely positive by looking at the area of the inhibition zone around the disc using a caliper.  This research shows that the diameter of the inhibition zone for Staphylococcus aureus at a concentration of 20% has an inhibition zone diameter of 8.71 mm, namely the medium category, a concentration of 40% has an inhibition zone diameter of 10.33 mm, namely the strong category, a concentration of 60% has an inhibition zone diameter. of 12,66 mm, namely the strong category, a concentration of 80% has an inhibitory zone diameter of 15,61 mm, namely the strong category. Based on the research results, it can be concluded that the ethanol extract of avocado leaves has activity to inhibit propionibacterium acne bacteria.